Surface fitting methods for modelling leaf surface from scanned data - M.N. Oqielat (Journal of King Saud University: Science, 2019)
Modelling leaves accurately is important in the improvement of a virtual plant model. Therefore an accurate illustration of the leaves are important which can be achieve via mathematical models. These models can be used to study biological procedures for instance, a canopy light environment or photosynthesis. In this research we proposed a new surface fitting method called Gaussion radial basis function Clough-Tocher method (RBF-CT) for modelling a leaf surface. The Gaussion RBF-CT method strategy based on joining the Gaussion radial basis function (RBF) and Clough-Tocher (CT) methods. The accuracy of the presented method is validated by applying it to scattered data taken from Franke (1982) as well as to a real scattered data set collected using a laser scanner from an Anthurium leaf (Loch, 2004). Our method is shown to produces a realistic representation of the leaf surface. Keywords: Interpolation, Finite elements methods, Virtual leaf, Radial basis function, Clough-Tocher method